Biofortified beans - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
For more than 300 million people, an inexpensive bowl of beans is the centerpiece of their daily diet. The common bean—Phaseolus vulgaris—is the world’s most important food legume, far more so than chickpeas, faba beans, lentils, and cowpeas. Given the widespread consumption of beans throughout the world, efforts to improve their micronutrient content could potentially benefit a great many people. Biofortifying the common bean will produce the greatest returns in areas where these beans supply a significant proportion of the nutrients in the diet. These areas include parts of East, Central and Southern Africa and all of Central America and Brazil.